Analysis of the Influence of Digital Marketing Strategies on Customer Loyalty in the Tiktok E-Commerce Industry - Pratiwi Seran, Yayuk; Ayuandira, Ririn; Patadungan, Hendriawan; Yanti, Rima; Asti, Asti (International Journal of Management Science and Information Technology, 2025)
This study aims to examine digital marketing strategies on customer loyalty in the e-commerce platform TikTok. The population of this study was all TikTok users aged 18–25, and according to Heir, the sample size was a minimum of 200. This study used a quantitative approach with primary data collected through an online questionnaire. Data analysis techniques included instrument testing, simple linear regression, and hypothesis testing, analyzed using SPSS 26. The t-test results indicated that digital marketing strategies had a positive and significant impact on customer loyalty. In Indonesia, TikTok has become one of the most popular social media platforms, with high penetration among the younger generation.